HR Marketing as a Supporting Tool of New Managerial Staff in Industry 4.0 - Kateřina Jančíková; František Milichovský (Administrative Sciences, 2019)
Human resource marketing (HRM) is focused on the creation of job-position while including all relevant parameters such as work specification, wage, and adequate communication of a job offer. Wage is possible to understand as not only the amount of money received but also as all kinds of reward for the work that has been completed. Forms of staff renumeration have received more interest during the last decade, especially in regards to managers and the concept of industry 4.0. Job offer descriptions help to find suitable applicants for specific managerial positions. The main objective of this paper is to state the relationship between gender and the chosen variables (job sources). For this purpose, there was a realized questionnaire survey, focused on HRM in the business environment in the Czech Republic. The sample population for the survey consisted of 522 people, though feedback was only received from 185 participants (a return rate of 35.44%). To process the data, we employed Pearson’s chi-square test for independence and cluster analysis. Graphical design was made using an ROC curve (Receiver Operating Characteristic). According to the results obtained, there were defined relationships between gender and job servers as job sources, and between gender and social networks as job sources. This dependence is supported by the ROC curve, which shows the expectations of wage incomes according to the work-experience of the employee.